Regeneration of urban cultural landscapes - Monisha Jain; Prafulla Parlewar (Ochrona Dziedzictwa Kulturowego, 2025)
The search for identity, the sense of belonging to a particular place, is a fundamental aspect of quality of life, whether the person is an inhabitant of a small village or an urban metropolis. The unique character of a place is woven into its townscapes and streetscapes, the interplay of layout and diversity of the spaces, the distinctive architectural character of buildings, and cultural values associated with it. A place's essence, which defines its identity, is remarkably delicate and susceptible to swift erosion. The rapid pace of urbanization, changing socio-economic values, increasing commercialization, and insensitive, generic development practices are eroding the quality of urban life.